Circadian Dysregulation: The Next Frontier in Obstructive Sleep Apnea Research. (11th September 2018) - von Allmen, Douglas C.; Francey, Lauren J.; Rogers, Garrett M.; Ruben, Marc D.; Cohen, Aliza P.; Wu, Gang; Schmidt, Robert E.; Ishman, Stacey L.; Amin, Raouf S.; Hogenesch, John B.; Smith, David F.
Abstract : Objective: To review the effects of the circadian clock on homeostasis, the functional interaction between the circadian clock and hypoxia‐inducible factors, and the role of circadian dysregulation in the progression of cardiopulmonary disease in obstructive sleep apnea (OSA). Data Sources: The MEDLINE database was accessed through PubMed. Review Methods: A general review is presented on molecular pathways disrupted in OSA, circadian rhythms and the role of the circadian clock, hypoxia signaling, crosstalk between the circadian and hypoxia systems, the role of the circadian clock in cardiovascular disease, and implications for practice. Studies included in this State of the Art Review demonstrate the potential contribution of the circadian clock and hypoxia in animal models or human disease. Conclusions: Molecular crosstalk between the circadian clock and hypoxia‐inducible factors has not been evaluated in disease models of OSA. Implications for Practice: Pediatric OSA is highly prevalent and, if left untreated, may lead to cardiopulmonary sequelae. Changes in inflammatory markers that normally demonstrate circadian rhythmicity are also seen among patients with OSA. Hypoxia‐inducible transcription factors interact with core circadian clock transcription factors; however, the interplay between these pathways has not been elucidated in the cardiopulmonary system. This gap in knowledge hinders our ability to identify potential biomarkers of OSA and develop alternative therapeutic strategies. A deeper understanding of the mechanisms by which OSA impinges on clock function and the impact of clock dysregulation on the cardiopulmonary system may lead to future advancements for the care of patients with OSA. The aim of this review is to shed light on this important clinical topic.